MEMAHAMI DAN MENGAPLIKASIKAN KONSEP DASAR PENELITIAN PUSTAKA BIDANG PENDIDIKAN - Syafriwana, Syafriwana (STAI YAPIS Takalar, 2022)
This journal aims to find out the basic concepts of library research in the field of education, to find out the application of the basic concepts of library research. Researchers can look for various existing references and this allows researchers to learn systematically in writing various scientific papers, by conveying ideas, with the aim that researchers are more critical and analytical in completing their research. Literature study is carried out before choosing a problem, with the aim of getting the most recent data. Therefore researchers must first conduct a literature review in order to obtain ideas in solving research problems.